(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Restorative justice is gaining increased attention as a rehabilitative and community-centered alternative to traditional punitive systems. Its core objective is to repair the harm caused by criminal behavior through the active participation of victims, offenders, and the broader community in the process of accountability, reconciliation, and making amends. This study utilized a descriptive research design with purposive sampling to assess the importance of restorative justice programs in Barangay Ugong, Valenzuela City. Thirty respondents—comprising 10 offenders, 10 victims, and 10 barangay council members—completed a survey questionnaire developed by the researchers. Data were analyzed using averages, percentages, a 4-point Likert scale, and ranking to interpret the responses. Among the 30 respondents, 36% (11 individuals) were aged 42 years and above. Female respondents accounted for 57% (17 out of 30), while 50% (15 respondents) had completed high school education. In assessing restorative justice processes, respondents strongly agreed with mediation (weighted mean = 3.43) and conciliation (weighted mean = 3.31), while arbitration received an overall agreement rating (weighted mean = 3.24). The most frequently reported challenge was the “insufficient understanding or consideration of the subject’s intentions, motivations, or context in decision-making,” cited by 27 respondents (16%). Among proposed solutions, the highest priority was “educate and engage the community to increase understanding and acceptance of restorative justice principles,” ranked first by 22 respondents (13%). Offenders were provided with clear, accessible informational materials outlining the benefits of restorative justice programs. A victim-centered campaign was developed to empower victims by explaining the program’s advantages. For the community, informational seminars, dialogues, and awareness campaigns were conducted to increase understanding. Barangay officials underwent in-depth training to strengthen and promote restorative justice principles and practices. Future research should focus on evaluating the long-term effects of these programs and conducting comparative studies to further assess their impact.